Proceeding of ICUDBE 2011 Sharing the World Musawah International Conference on Universal Design in Built Environment (ICUDBE2011) - Abdul Rahim, Asiah (KAED Universal Design Unit (KUDU), 2011)
International Conference on Universal Design in Built Environment (ICUDBE2011), proceeding